2021
DOI: 10.1186/s12862-021-01819-4
|View full text |Cite
|
Sign up to set email alerts
|

Searching for signatures of positive selection in cytochrome b gene associated with subterranean lifestyle in fast-evolving arvicolines (Arvicolinae, Cricetidae, Rodentia)

Abstract: Background Mitochondrial genes encode proteins involved in oxidative phosphorylation. Variations in lifestyle and ecological niche can be directly reflected in metabolic performance. Subterranean rodents represent a good model for testing hypotheses on adaptive evolution driven by important ecological shifts. Voles and lemmings of the subfamily Arvicolinae (Rodentia: Cricetidae) provide a good example for studies of adaptive radiation. This is the youngest group within the order Rodentia showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…The CYTB gene shows a significant difference in ω levels between subterranean and aboveground species and confirmed selection relaxation for Ellobius species and L. mandarinus . These results reproduce our earlier findings performed in the analysis of the CYTB alone and with a different set of compared species [ 34 ]. In addition to those previously reported, we have now detected positively selected sites for P. schaposchnikowi , Ellobius species, L. mandarinus, and H. fertilis .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The CYTB gene shows a significant difference in ω levels between subterranean and aboveground species and confirmed selection relaxation for Ellobius species and L. mandarinus . These results reproduce our earlier findings performed in the analysis of the CYTB alone and with a different set of compared species [ 34 ]. In addition to those previously reported, we have now detected positively selected sites for P. schaposchnikowi , Ellobius species, L. mandarinus, and H. fertilis .…”
Section: Discussionsupporting
confidence: 91%
“…Finally, Tomasco and Lessa [ 66 ] found increased values of ω in COX2 of subterranean coruros Spalacopus (almost 30×) and tuco-tucos Ctenomys (11×) relative to aboveground octodontoids. Our previous studies on the Arvicolinae subfamily also showed the relaxation of selection strength in CYTB reflecting an increased ratio (ω) in subterranean lineages compared to non-subterranean lineages [ 34 ]. Later, indicated changes were demonstrated for all mitochondrial protein-coding genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the transition to the subterranean lifestyle within this subfamily occurred more than once. Our previous studies showed that selection pressure is relaxed at the mitochondrial CYTB gene in particular (Bondareva et al, 2021a), and in mitochondrial genomes for most subterranean Arvicolinae species (Bondareva et al, 2021b). The recent and phylogenetically independent transition of Arvicolinae voles to subterranean lifestyle makes it possible to trace adaptive events at a smaller evolutionary scale, in contrast to the analysis of classical ancient subterranean species such as Heterocephalus Rüppell, 1842, Nannospalax Palmer, 1903, and Fukomys Ogilby, 1838.…”
Section: Introductionmentioning
confidence: 99%